2006
DOI: 10.1186/1476-4598-5-18
|View full text |Cite
|
Sign up to set email alerts
|

Functional studies of BCL11A: characterization of the conserved BCL11A-XL splice variant and its interaction with BCL6 in nuclear paraspeckles of germinal center B cells

Abstract: Background: Chromosomal aberrations of BCL11A at 2p16.1 have been reported in a variety of B-cell malignancies and its deficiency in mice leads to a profound block in B-cell development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
57
0
3

Year Published

2008
2008
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 74 publications
(63 citation statements)
references
References 39 publications
3
57
0
3
Order By: Relevance
“…We previously observed that in B cells, exogenous or ectopically overexpressed BCL11A-XL accumulated primarily within nuclear matrix paraspeckles (37). As with those results, we observed localization indistinguishable from that following ectopic delivery of GFP-BCL11A-XL or GFP-BCL11A-XL-K5/A into 293T cells (Fig.…”
Section: Bcl11a-xl Modulates Rag Expressionsupporting
confidence: 69%
See 3 more Smart Citations
“…We previously observed that in B cells, exogenous or ectopically overexpressed BCL11A-XL accumulated primarily within nuclear matrix paraspeckles (37). As with those results, we observed localization indistinguishable from that following ectopic delivery of GFP-BCL11A-XL or GFP-BCL11A-XL-K5/A into 293T cells (Fig.…”
Section: Bcl11a-xl Modulates Rag Expressionsupporting
confidence: 69%
“…4B and C and data not shown). This motif defines a superfamily of TFs crucial to the development of several hematopoietic lineages (23,25,37,41,55) (Fig. 1B).…”
Section: Figmentioning
confidence: 99%
See 2 more Smart Citations
“…The SNP with the largest effect size is located in the second intron of a gene on chromosome 2, BCL11A. Although BCL11A has been investigated in the context of lymphocyte development (8,9), its role in the red blood cell lineage has not been previously assessed.…”
mentioning
confidence: 99%